Reusing of intraoperative exfoliated finger epidermis in the treatment of hand scar contracture in patients with RDEB - Chong Wu; Teng Guo; Yuluo Jian; Xinhe Jiao (Scientific Reports)
Abstract Patients with recessive dystrophic epidermolysis bullosa (RDEB) frequently develop pseudosyndactyly due to recurrent hand blistering and subsequent scar contracture. Conventional release surgery typically employs allogeneic biological dressings or synthetic materials for wound isolation, yet existing approaches are associated with frequent dressing changes, prolonged healing cycles, and secondary trauma. This study pioneers the clinical application of intraoperatively shed epidermal tissue for fabricating autologous epidermal finger cuffs to cover post-surgical defects, evaluating its therapeutic efficacy. 13 RDEB patients with hand contractures were stratified into experimental (n = 6, autologous epidermal finger cuffs) and control (n = 7, traditional petrolatum gauze dressings) cohorts following standardized contracture release procedures. Outcome measures included wound healing time, dressing change frequency, hemorrhage during dressing changes (VAS scale), and 6-month functional assessments. The experimental cohort demonstrated significantly accelerated wound closure versus controls (19.0 ± 1.5 vs. 29.0 ± 2.5 days, U = 3.0, p = 0.002), with median healing time reduced by 34.5%. Experimental subjects required 50% fewer median dressing changes (W = 42, p = 0.004) and exhibited 55% lower hemorrhage VAS scores (U = 4.0, p = 0.001), with strong positive correlation between VAS scores and dressing frequency (r = 0.78, p < 0.01). Safety profiles showed no severe infections: experimental group reported 1 case (16.7%) of epidermal displacement requiring reinforcement, versus 2 control cases (28.6%) with mild inflammation. Six-month follow-up revealed 24% lower median finger webbing space depth loss in experimental group (1.9 mm vs. 2.5 mm), though statistically non-significant (U = 15, p = 0.35). Neither group exhibited contracture recurrence or significant functional improvement. This novel technique repurposes intraoperatively discarded epidermal tissue as biological dressings, effectively minimizing secondary trauma from adherent dressing removal. It presents a clinically superior alternative for RDEB management, characterized by reduced treatment burden and accelerated recovery.